∫ 0 ∞ 1 + x 2 arcsin ( 1 + x 2 2 x ) d x = b π a Find a + b , if both are integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sorry for careless mistake!
I = ∫ 0 ∞ 1 + x 2 arcsin ( 1 + x 2 2 x ) d x = ∫ 0 π 2 arcsin ( sin θ ) d θ = 2 1 ( ∫ 0 2 π arcsin ( sin θ ) d θ + ∫ 2 π π arcsin ( sin θ ) d θ ) = 2 1 ( ∫ 0 2 π θ d θ + ∫ 2 π π ( π − θ ) d θ ) = 2 1 ( 2 θ 2 ∣ ∣ ∣ ∣ 0 2 π + [ π θ − 2 θ 2 ] 2 π π ) = 2 1 ( 8 π 2 − 0 + π 2 − 2 π 2 − 2 π 2 + 8 π 2 ) = 8 π 2 Let x = tan 2 θ ⟹ d x = 2 1 sec 2 2 θ d θ then sin θ = 1 + x 2 2 x Note that − 2 π ≤ arcsin x ≤ 2 π
Therefore, a + b = 2 + 8 = 1 0 .
First multiply by 2 in the integrand and 1/2 outside of it is the same thing as multiplying by 1. Recognizing that 2x/1+x^2 and 2/1+x^2 are just reversed versions of sin(x) and dx with regard to the Tangent-Half Angle Substitution allows us to perform the so-called "Reverse Weierstrass" substitution. So we end up having 1/2 times the integral of u du (Note: Since the bounds are in the domain of the arcsine function, then arcsin(sin(u)) = u), from 0 to pi/2 which equals pi^2/(4*2) = pi^2 / 8. Then 2 + 8 = 10, as desired.
Problem Loading...
Note Loading...
Set Loading...
∫ 0 ∞ 1 + x 2 arcsin ( 1 + x 2 2 x ) d x = ∫ 0 1 1 + x 2 arcsin ( 1 + x 2 2 x ) d x + ∫ 1 ∞ 1 + x 2 arcsin ( 1 + x 2 2 x ) d x
Then, ∫ 1 ∞ 1 + x 2 arcsin ( 1 + x 2 2 x ) d x = ∫ 1 0 1 + u 2 arcsin ( 1 + u 2 2 u ) − d u = ∫ 0 1 1 + u 2 arcsin ( 1 + u 2 2 u ) d u by change x = u 1
∫ 0 ∞ 1 + u 2 arcsin ( 1 + u 2 2 u ) d u = 2 ⎝ ⎜ ⎛ ∫ 0 1 1 + u 2 arcsin ( 1 + u 2 2 u ) d u ⎠ ⎟ ⎞
Now, change u = tan ( 2 y ) . Thus the integral become
∫ 0 2 π 2 y d y = 4 y 2 = 1 6 π 2
∫ 0 ∞ 1 + u 2 arcsin ( 1 + u 2 2 u ) d u = 2 ⎝ ⎜ ⎛ ∫ 0 1 1 + u 2 arcsin ( 1 + u 2 2 u ) d u ⎠ ⎟ ⎞ = 2 × 1 6 π 2 = 8 π 2